Pengaruh Customer Experience, Ease Of Use Terhadap Intention to Reuse Application melalui Customer Satisfaction pada Pengguna Layanan Pengantar Makanan Go-Food di Yogyakarta (Penelitian Kasus pada Pengguna Go-Food di Daerah Istimewa Yogyakarta) - Sadewa, Alex Fitrianta; Udayana, Ida Bagus Nyoman; Cahyani, Putri Dwi (Ekonomis: Journal of Economics and Business, 2024)
This study aims to examine the effect of customer experience, ease of use on intention to reuse applications through customer satisfaction in users of Go-Food food delivery services. The method in this study uses a quantitative method and has a population of Yogyakarta people who use Go-Food services, with a total sample of 106 respondents. The analytical method used is IBM SPSS Statistics 25. The results show that customer experience has a positive and significant effect on customer satisfaction. Then ease of use has a positive and significant effect on customer satisfaction. The customer experience variable has a positive and significant effect on intention to reuse applications. Furthermore, the variable ease of use has a positive and significant effect on the intention to reuse application. And customer satisfaction has a positive and significant effect on the intention to reuse application.